Journal of clinical bioinformatics (Biomed Central Ltd., 2011)
"JCBi aims to elucidate how biological and medical information can be applied to the development of personalized healthcare, medication and therapies. JCBi is a forum for the translation of bioinformatics and computational methods into clinical and medical applications, as well as the advancement of our understanding of the molecular and cellular mechanisms of diseases."